Adopting building information modelling (BIM) into industrialised building system (IBS) in Malaysian construction industry / Irma Hanie Ibrahim ... [et.al.] - Ibrahim, Irma Hanie; Tuanku Karim, Sharifah Fitrah; Ismail, Noor Akmal Adillah; Syed Jamaludin, Shariffah Zatil Hidayah (Universiti Teknologi MARA Cawangan Sarawak, 2022)
Building Information Modelling (BIM) is the development of digital models used during planning, design, construction, and operation stages of a project. Some construction players doubt the practicality in implementing this new technology. Full adoption of Industrialised Building System (IBS) project is not an easy journey. In addition, the implementation of BIM technology into IBS system will put the client's expectation at risk as it is difficult to understand the complex software. Therefore, the aim of this research is to explore the adoption of BIM into IBS application in Malaysian construction industry. Among the objectives of this research are to investigate the implementation of BIM into IBS application, examine challenges in implementing BIM into IBS application and propose ways to improve the incorporation of BIM into IBS application by Malaysian construction industry players.